Genetic and phenotypic characterisation of clinical methicillin-resistant staphylococcus aureus in a Malaysian hospital / Lim King Ting - Lim, King Ting (2012)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the main bacterial pathogens responsible for a variety of nosocomial infections ranging from soft-tissue infections to bacteremia. Since most MRSA is often resistant to multiple antibiotics, this has raised a concern over the limited choice of antimicrobial-agents for treatment of life-threatening cases. The objectives of this study were to determine the antimicrobial resistance profiles, presence of resistance and virulence genes, to investigate the molecular epidemiology of MRSA and their evolution over a six-year period. The antibiograms of 188 MRSA strains isolated from UMMC were analyzed by disk-diffusion test and minimum inhibitory concentrations. The agr and SCCmec types, presence of resistance and virulence genes were determined by PCR, genetic diversity by PFGE, coa-RFLP, MLST, spa and dru typing and molecular evolution by MLST-spa-dru types. All the strains were sensitive to vancomycin. They showed high resistance (≥80%) towards ciprofloxacin, clindamycin, erythromycin and gentamicin. A significant increase (P<0.05) in resistance rates towards trimethoprim-sulfamethoxazole, netilmicin and tetracycline between 2003 and 2008 was observed. blaZ gene was detected in all strains whereas ermA, aac(6’)-aph(2”), tetM, ermC, tetK, ileS, msrA and mupA specific amplicons were detected in 157(84%), 156(83%), 92(49%), 40(21%), 39(21%), 10(5%), 4(2%) and 2(1%) strains, respectively. blaZ, tetM, ermC, tetK, ileS2 and mupA genes were plasmid-encoded. Double mutations in rpoB gene were associated with high rifampicin-resistance while mutational change 461Leu/Lys in fusA gene was associated with high fusidic acid-resistance. The prevalence of sea, sec and ica among strains isolated in 2008 increased significantly (P<0.05) compared to 2003. pvl gene was detected in 2007 and 2008 strains. Three SCCmec types (SCCmec type III, 90%; SCCmec type IV, 9%; SCCmec V, 1%) and iii three agr types (agr type-I, 97.5%; agr type-II, 1.2%; agr type-III, 0.6%) were observed. coa-RFLP, PFGE, MLST, spa and dru typing subtype the strains into 47 profiles, 85 PFPs, 10 MLST, 17 spa and 30 dru types, respectively. Some strains from six-years apart shared similar DNA profiles, indicating the persistence of a particular genotype. The predominant MLST type, ST239 (83.5%) was further distinguished to seven different spa and 26 different dru types, including 17 novel dru types. Maximum parsimony tree based on dru repeats revealed that 10 dru types (dt11am, dt13j, dt15n, dt13q, dt13n, dt13p, dt13f, dt13ao, dt12j, dt7v) shared similar MLST-spa type with dt13d, suggesting that they might have evolved from ST239-t037-dt13d. Clone ST239-t037-dt13g and 32 other MRSA clones being introduced in 2007-2008 had replaced ST239-t037-dt13d and nine MRSA clones present in 2003. In conclusion, the prevalence of resistance and virulence factors had increased over a six-year period. The association of resistance genes with mobile genetic elements possibly enhances the spread of resistant traits in MRSA. Correlation between DNA profiles (PFGE and coa-RFLP) and resistotypes was observed. ST239-t037-dt13d along with other MRSA clones in 2003 was replaced by ST239-t037-dt13g and other new emerging spa and dru types. The data from this study may act as a reference for monitoring mupirocin, rifampicin, fusidic acid and the prevalence of virulence among Malaysian MRSA strains over a longer period of time.